2011
DOI: 10.1308/003588411x12851639106954
|View full text |Cite
|
Sign up to set email alerts
|

How does the media profile of cancer compare with prevalence?

Abstract: INTRODUCTION Knowledge and understanding of disease can influence time to presentation and potentially, therefore, cancer survival rates. The media is one of the most important sources of public health information and it influences the awareness and perception of cancer. It is not known if the reportage of cancer by the media is representative to the true incidence of disease. MATERIALS AND METHODS The top 10 UK daily newspapers were assessed over a 1-year period for the 10 most common UK cancers via their on-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 15 publications
2
30
0
1
Order By: Relevance
“…The mass media, especially television and magazines, can significantly affect the frequency of dermoscopic examination and encourage desired, health-promoting behaviors in the key target-group audience [21]. However, an analysis of the top ten most-read newspapers in the United Kingdom revealed that in relation to the incidence of melanoma, there was an over-representation of articles dedicated to melanoma in the tabloids, while the number of publications in the so-called opinion-forming press was relatively low [22]. Among the 2,659 participants of Sweden’s 2008 “Euromelanoma Day”, the majority (1,623) gained knowledge about this campaign from the press (61%), by word of mouth (326 or 12%), or from the Internet (187 or 7%), radio (133 or 5%) and television (110 or 4%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…The mass media, especially television and magazines, can significantly affect the frequency of dermoscopic examination and encourage desired, health-promoting behaviors in the key target-group audience [21]. However, an analysis of the top ten most-read newspapers in the United Kingdom revealed that in relation to the incidence of melanoma, there was an over-representation of articles dedicated to melanoma in the tabloids, while the number of publications in the so-called opinion-forming press was relatively low [22]. Among the 2,659 participants of Sweden’s 2008 “Euromelanoma Day”, the majority (1,623) gained knowledge about this campaign from the press (61%), by word of mouth (326 or 12%), or from the Internet (187 or 7%), radio (133 or 5%) and television (110 or 4%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…By creating new methods to identify and capture cases from these settings, both the community-based hospital cancer registry and the state cancer surveillance programs will benefit. There is also a potential benefit to public health where lack of awareness of the significance of these diseases may result in delays in diagnosis and treatment that could impact survival [47].…”
Section: Resultsmentioning
confidence: 99%
“…; and can this framing be explained by media routines and conventions? The homogeneity of the coverage in a relatively small number of media outlets could be explained by the media's tendency to shy away from covering bowel cancer (Gerlach et al 1997, Lewison et al 2008, MacKenzie et al, 2010, Williamson et al, 2011, Konfortion et al 2014, perhaps due to prurience about discussing bowels or bowel cancer symptoms and a general taboo associated with the disease.…”
Section: Discussion: Responsibilising Eaters Through the Mediamentioning
confidence: 99%
“…Lewison et al (2008) showed that more than a third of cancer research featured on the BBC website mentioned breast cancer (compared to a disease burden of 13%) with the next most covered cancer sites being lung and prostate cancer -noting that lung cancer was much less covered than its disease burden of almost 20% would have suggested. In the case of bowel cancer the media have been shown to shy away from covering this topic, perhaps due to prurience about discussing bowels or bowel cancer symptoms, with bowel cancer receiving disproportionate coverage compared to its disease burden (Gerlach et al, 1997, Lewison et al 2008, MacKenzie et al 2010, Williamson et al, 2011, Konfortion et al 2014. A key question for this current paper is to further explore the press coverage of bowel cancer by examining how nutrition discourse about bowel cancer is mediated by the UK press.…”
Section: Nutrition and Geographies Of Responsibilitymentioning
confidence: 99%